Corak Pemikiran Nurcholish Madjid dalam Bingkai Politik Kebangsaan di Indonesia: Nurcholish Madjid's Thought Patterns in the Framework of National Politics in Indonesia - Hidayatulloh, Taufik; Muna, Izzul (Jurnal Filsafat Indonesia, 2024)
The process of seeking meaning within oneself is a deep and often complex journey involving various psychological, emotional, and philosophical aspects. This includes when an individual interprets themselves as a volunteer. This study explores the experiences and life meanings of social volunteers in Bali through the lens of Jean-Paul Sartre's existentialism. The data for this research was collected through in-depth interviews with three informants, selected using snowball sampling techniques. The interview results were then analyzed using Sartre's existentialist perspective. The findings, related to the principle that "existence precedes essence," suggest that volunteers in this study are able to find meaning in themselves through the experiences they gain while existing as volunteers. Regarding the experience of etre en soi (being-in-itself), volunteers have the capacity to manipulate various facts to preserve their existence. The form of manipulation observed is through neglect that occurs when volunteers experience discrediting by their surrounding social environment. The experience of etre en soi faced by volunteers does not lead them to feel they are in a state of 'bad faith' (mauvaise foi). Volunteers in this study can be considered existentialists, possessing a dimension of authenticity within themselves. These volunteers do not perceive their engagement in social activities as a form of coercion but rather as a willingness to fulfill their instinct for freedom.